Differentiated Learning Oriented to Four Aspects of Multiculturalism in Strengthening the Dimension of Global Diversity in Elementary Schools - Arum Aprilasyarma; Maharani Putri Kumalasani (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to explain the integration of multicultural learning strategies and differentiated instruction in strengthening the global diversity dimension within the Pancasila Student Profile at the elementary school level. The research employs a qualitative method with a descriptive approach to provide an in-depth description of learning processes and strategies in elementary school settings. The study was conducted at four public elementary schools in the Samarinda Ulu District over a period of two months, with the primary participants comprising fourth-grade teachers and students. Data were collected through observation, interviews, documentation, and questionnaires, and were analyzed thematically. Grounded in James Banks’ theory of multicultural education, this study covers four dimensions: content integration, knowledge construction, prejudice reduction, and equity pedagogy. The findings indicate that the integration of local and national cultural content plays the most significant role in fostering students’ global diversity awareness. Differentiated instruction, which involves variations in content, process, and product, promotes inclusivity by allowing diverse expressions of student identity and learning styles. However, challenges remain within the equity pedagogy dimension due to limited learning resources and teacher readiness. Overall, the combination of these two approaches proves effective in developing students’ tolerant, empathetic, and globally minded character.